GAP-43 closely interacts with BDNF in hippocampal neurons and is associated with Alzheimer's disease progression - Ye Ji Lee; Ye Ji Jeong; Eun Ji Kang; Beom Seok Kang; Song Hee Lee; You Jin Kim; Seong Su Kang; Sang Won Suh; Eun Hee Ahn (Frontiers in Molecular Neuroscience, 2023)
IntroductionGrowth-associated protein 43 (GAP-43) is known as a neuronal plasticity protein because it is widely expressed at high levels in neuronal growth cones during axonal regeneration. GAP-43 expressed in mature adult neurons is functionally important for the neuronal communication of synapses in learning and memory. Brain-derived neurotrophic factor (BDNF) is closely related to neurodegeneration and synaptic plasticity during the aging process. However, the molecular mechanisms regulating neurodegeneration and synaptic plasticity underlying the pathogenesis and progression of Alzheimer's disease (AD) still remain incompletely understood.MethodsRemarkably, the expressions of GAP-43 and BDNF perfectly match in various neurons in the Human Brain Atlas database. Moreover, GAP-43 and BDNF are highly expressed in a healthy adults' hippocampus brain region and are inversely correlated with the amyloid beta (Aβ), which is the pathological peptide of amyloid plaques found in the brains of patients with AD.ResultsThese data led us to investigate the impact of the direct molecular interaction between GAP-43 and BDNF in hippocampal neuron fate. In this study, we show that GAP-43 and BDNF are inversely associated with pathological molecules for AD (Tau and Aβ). In addition, we define the three-dimensional protein structure for GAP-43 and BDNF, including the predictive direct binding sites via analysis using ClusPro 2.0, and demonstrate that the deprivation of GAP-43 and BDNF triggers hippocampal neuronal death and memory dysfunction, employing the GAP-43 or BDNF knock-down cellular models and 5XFAD mice.ConclusionThese results show that GAP-43 and BDNF are direct binding partners in hippocampal neurons and that their molecular signaling might be potential therapeutic targets for AD.